Concepções de tecnologia de graduandos do estado de São Paulo e suas implicações educacionais: breve análise a partir de modelagem de equações estruturais - Veraszto, Estéfano Vizconde; Silva, Dirceu da; Camargo, Eder Pires de [UNESP]; Barros Filho, Jomar (FapUNIFESP (SciELO), 2013)
This paper presents some results from a study of undergraduate students from different regions of the State of São Paulo that sought to better understand the relationships between society and perceptions and attitudes towards technological development. Noting that the media, academia and official documents regulating education understand and present the technology in a distinct and often contradictory ways, this paper seeks to review existing literature on the different ways to conceptualize this term, and thereafter, to develop a Likert' scale for mapping the concepts of students. Using the confirmatory analysis of structural equation modeling, this research concludes that the sample studied shows a classical view, but outdated, what means technology, by linking it to science and technology without distinction or critical viewpoints.

Este trabalho apresenta parte dos resultados de uma pesquisa desenvolvida com alunos de graduação de diferentes regiões do Estado de São Paulo, que buscou entender melhor as relações entre a sociedade e as concepções e atitudes frente ao desenvolvimento tecnológico. Constatando que mídia, academia e documentos oficiais que regulamentam a educação entendem e apresentam a tecnologia de forma distinta e, muitas vezes, contraditórias, este trabalho busca fazer uma revisão bibliográfica sobre as diferentes formas de conceituar este termo, para, a partir de então, desenvolver uma escala de Likert para o mapeamento das concepções de estudantes. Utilizando a análise confirmatória da Modelagem de Equações Estruturais, este trabalho conclui que a amostra pesquisada apresenta uma visão clássica, mas ultrapassada, do que venha a ser a tecnologia, associando ciência e técnica sem distinções ou pontos de vistas críticos.
Conceptions of technology of graduates of the State of Sao Paulo and its implications for education: brief analysis based on structural equation modeling
Keywords: Technology; Structural equation modeling; STS studies; Tecnologia; Modelagem de equações estruturais; Estudos CTS